Zambia : A Review of the World Bank Group Jobs Portfolio - Krishnan, Sudha Bala; Peterburs, Teresa (Washington, DC: World Bank, 2017)
This report analyzes the World Bank Group (WBG) portfolio in Zambia focused on jobs, referred to as the jobs portfolio, regarding its impact on outcomes related to job creation, job quality, and job access. The review is presented within the context of Zambia’s jobs priorities: more good-quality jobs with traditionally disadvantaged groups benefitting from opportunities to work. It finds that the jobs portfolio is more focused on intermediate-level outcomes related to jobs, such as improving access to markets and firm performance. A range of intervention types contributes to job creation (66 percent of the reviewed portfolio), job quality (47 percent), and job access (51 percent). Activities focused on spatial development in value chains tend to support job creation in the formal sector. Job quality outcomes include enhanced worker productivity in informal agriculture where the majority of Zambians still work. The WBG has primarily supported job access through targeted interventions in lagging regions. Further, the combined portfolios of the WBG and let’s work partners show greater coverage of a range of job quality and job access outcomes. Areas for future support to improve job outcomes include macroeconomic and regulatory support, skills development, and targeted support for vulnerable populations and youth in particular. In addition, projects need to be reinforced by sound monitoring and evaluation (M and E) systems tracking results explicitly related to jobs.